Implementation of Government Policy in the Distribution of BLT (Cash Trans - Fatimah, Sri; Haris, Subhan (ann4publisher@gmail.com, 2023)
The condition of the people experiencing the problem of a prolonged poverty crisis made the government take swift action by issuing a BLT (cash transfer) policy to go through several community groups so that the community would be more prosperous. This study aimed to determine the implementation of village government policies in the distribution of BLT in Jambe Village, Kertasemaya District, Indramayu Regency. This research uses a qualitative description approach. The data collection technique uses primary data and secondary data. Informant selection techniques in this study used purposive sampling techniques and snowball techniques. The results of the research are as follows: First, the communication carried out by the village government in implementing the policy of providing BLT is considered clear enough so that the community can understand this assistance. Second, the resources for implementing BLT to the community follow what has been determined, and there is plenty. Third, the disposition in implementing BLT is carried out according to existing regulations. Fourth, the bureaucratic structure in implementation uses the village government structure.